Studi Analitis Peristiwa Isra’ Mi’raj Nabi Muhammad SAW dalam Pendekatan Sains - Achmad, Fatoni; Ivonia, Ivonia (MOMENTUM : Jurnal Sosial dan Keagamaan, 2018)
About 1400 years ago, we heard of a great event from the Arab land, Isra 'Mi'raj. However, over time, and the times are gettingbetter with increasing science theory. Then the events of Isra and Mi'raj can be revealed in modern physics so that they can be accepted by human reason. Through Einstein's theory of relativity, E = m.c2 (where E is energy, m is mass, and c is the speed of light), Isra' Mi'raj becomes an event that is no longer irrational, but rational and scientific. Then, on what part of the theory of relativity play a role in explaining the events of Isra 'and Mi'raj of the Prophet Muhammad SAW scientifically? All will be explored comprehensively and systematically in this paper